Sutras as a Genre of World Literature: Thoughts on Translation, Translatio, and Poetry as Movement. Issue 3 (2nd July 2016) - Eubanks, Charlotte
ABSTRACT: This article thinks through the Buddhist sutra as a mode of world literary production from the second century CE to the present. I argue for understanding the sutra as a site of remediation and as a massively open-ended textual project aimed at articulating expressions of insight.